Research Skills in Teachers' Training Education: Perceptions and performance - Ana Mendioroz Lacambra; María Napal Fraile; Alicia Peñalva Vélez (Universidad Autónoma de Baja California, 2022)
Research competence is essential for basic scientific literacy; if trained from early childhood, it enhances the ability of the learner to elaborate explanations, stemming from inquiry and following theoretical construction. So far, most of the research devoted on teachers' research competence has been focused on theoretical questions. Thus, the objective of this work is to get 208 student teachers to estimate their research competence and to compare it to their actual performance. Students' perceptions were measured using a questionnaire that referred to the skills and abilities included in the research competence. Their real performance was assessed through four specific tasks, which mobilized the four types of thinking required for the development of this competence: comprehensive, critical, creative and metacognitive. The results show that students' beliefs do not generally adjust to their real performance and that therefore they are unaware of their training needs, which is essential for learning to learn.